2009
DOI: 10.1002/ebch.462
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane review: Interventions for treating obesity in children

Abstract: BackgroundChild and adolescent obesity is increasingly prevalent, and can be associated with significant short‐ and long‐term health consequences.ObjectivesTo assess the efficacy of lifestyle, drug and surgical interventions for treating obesity in childhood.Search strategyWe searched CENTRAL on The Cochrane Library Issue 2 2008, MEDLINE, EMBASE, CINAHL, PsycINFO, ISI Web of Science, DARE and NHS EED. Searches were undertaken from 1985 to May 2008. References were checked. No language restrictions were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 258 publications
1
97
1
2
Order By: Relevance
“…The World Health Organization has rated the evidence for energy density of the diet (calculated as energy divided by weight of solid food and liquids consumed as food) and intake of sugar from sugar-sweetened beverages (E%) (including fizzy lemonade, ice tea, lemonade; exclusive cocoa milk, soy and oat beverages) to be linked to weight gain as convincing and probable, respectively (17). Although there is still some discussion whether these dietary factors do lead to obesity (18), these were used in the analyses as proposed dietary risk factors for obesity together with added sugar (E%).…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization has rated the evidence for energy density of the diet (calculated as energy divided by weight of solid food and liquids consumed as food) and intake of sugar from sugar-sweetened beverages (E%) (including fizzy lemonade, ice tea, lemonade; exclusive cocoa milk, soy and oat beverages) to be linked to weight gain as convincing and probable, respectively (17). Although there is still some discussion whether these dietary factors do lead to obesity (18), these were used in the analyses as proposed dietary risk factors for obesity together with added sugar (E%).…”
Section: Methodsmentioning
confidence: 99%
“…4,5 However, slow progress in learning how to effectively prevent 6 and treat 7 it may reflect fundamental lack of knowledge as to what predicts successful long-term weight loss in children.…”
mentioning
confidence: 99%
“…Some previous studies found a significant effect of 6 months of weight-management programs on lowering BMI [44]. Also, interventions of 10 to 12 weeks of weight-management program have significant reduction of BMI of obese adolescents [45]. In contrast, after 12 months of standard obesity rehabilitation plus planned individual PA, an improvement was observed in the PA of obese patients but no reduction of body weight compared with standard care [46].…”
Section: Bmi Before and After Treatmentmentioning
confidence: 87%